Antimicrobial Test of Telang Flower Extract (Clitoria ternatea L.) against the Growth of Candida albicans - Anas Fadli Wijaya; Rian Anggia Destiawan; Nosa Ika Cahyariza (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Candidiasis is an acute and subacute fungal infection caused by the Candida group, especially Candida albicans. Infectious diseases due to microbes can be treated using modern drugs, namely antifungals. In some cases, antimicrobials often develop resistance due to improper administration. The occurrence of such resistance encourages further research on new active ingredients that can be used as antimicrobial alternatives, especially from plant sources containing flavonoids. The purpose of this study is to determine the effect of antimicrobial content of ethanol extract 70% of Telang flowers on the growth of C. albicans. This research is a laboratory experimental research with post test control group design only method. Determination of antimicrobial activity is carried out by the pitting method. Telang flower extract that has been diluted with 10% DMSO, taken as much as 30µl then dripped into the well. Positive control using antimicrobial ketocenazole and negative control using DMSO 10% which was dripped on the well as much as 30µl. Based on the results of observations, the inhibition zone is only formed in positive control with an average of 15.5 + 0.4 mm. The results of ethanol extract of 70% Telang flowers that have been conducted did not show antimicrobial activity against fungal growth C. albicans. The absence of this inhibitory zone is due to the unknown concentration of active compounds of Telang flowers that are responsible as antimicrobials, so it is necessary to conduct research on the search for concentrations of active compounds that have the ability as antimicrobials.